(3LRA aj GdCUhds - (3Ydj Hf Ybjd Hf eMeO Hf Ybjd GdHZOGOj GdXaQj, CHh GdhaGA, jYQa HGHf Ybjd,J (B513 (3g` s
(3ChdgG (B:s
(3hgPGf ef LedI eG PgHJ Gdjg hGSJOdhG Ydi UMJg HeG QeRhG ef Pdc s
(3BNQgG (B:s
(3jbhdhG cja hgPG CeQ Cgd GdYde GdPi CNJGQhg s
(3JcQQJ CjVkkG JMJ Qbe (B42 (3CUhds
(3bdjd GdfbWs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B313 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B151s
(3eUOQ GbJfGA GdCUd (B:s
(3GdXGgQjI HOeTb (B((3MOjK (B245(30)) s
Keywords: (3CUhd Gdabgs